IC 9388 Materials Flow Of Tungsten In The United States - Gerald R. Smith (The National Institute for Occupational Safety and Health (NIOSH), 1994)
Because of continuing concerns regarding the effects of cumulative quantities of materials in the environment, the Bureau of Mines has initiated a series of studies to evaluate, to the fullest extent possible, all aspects of the materials flow sequence fur selected commodities. Although tungsten and its compounds do not pose a significant health hazard to the environment, they do represent valuable resource materials to which appropriate conservation considerations must be given. The present study includes a description of recent trends in the consumption, loss, and recycling of tungsten-containing materials in the United States during the period 1974 to 1991 and an estimation of the cumulative loss of tungsten to the environment since 1910. Obsolete tungsten is recycled primarily as cemented tungsten carbide components that have been used in cutting and wear-resistant applications. The quantity recycled, as a of annual U.S. consumption of tungsten, was estimated to have increased from 10% in 1974 to 341a in 1991. An estimated 58% of the 148,000 metric tons of primary tungsten consumed since 1910 was lost to the environment through means such as dissipation, discard, and dilution.